Improving social functional text writing in Thai nursing students through contextual teaching and learning: Insights from classroom action research - Priyandara, Shana Noor Izza; Soviyah, Soviyah; Agustina, Noor Qomaria; Lassamano, Hamidah (Teaching English as a Foreign Language Journal, 2024)
This study explores the implementation of the Contextual Teaching and Learning (CTL) approach to enhance social functional text writing skills among nursing students at Fhisrinthon Nursing School, Yala, Thailand. Social functional texts, such as patient reports and healthcare instructions, are essential for effective communication in nursing. The research investigates: (1) How is the CTL approach implemented to improve nursing students' writing of social functional texts? (2) What improvements in writing abilities and engagement are observed under the CTL approach? Using a classroom action research design, the study follows two iterative cycles of planning, action, observation, and reflection. Participants include 15 nursing students, with data collected through writing tasks, classroom observations, interviews, and reflective journals. Writing scores are analyzed quantitatively, while qualitative data are examined thematically. Findings indicate that the CTL approach, integrating real-life nursing contexts, significantly improves students’ writing. Key strategies include aligning learning objectives with nursing-specific materials, vocabulary building, dialogue creation, and role-play activities in simulated hospital settings. Writing scores improved from 67.2 (pretest) to 75 (Cycle 1) and 78.6 (Cycle 2). Students also reported increased motivation, engagement, and satisfaction with the learning process. This research highlights the effectiveness of the CTL approach in nursing education, demonstrating its role in enhancing both writing skills and communication competencies essential for nursing practice. It offers practical insights for educators integrating contextually relevant teaching methods into English language instruction for healthcare professionals.